2012
DOI: 10.2298/abs1201265m
|View full text |Cite
|
Sign up to set email alerts
|

Trace element concentrations in wild mussels from the coastal area of the southeastern Adriatic, Montenegro

Abstract: The aim of the present investigation was to quantify the levels of trace elements (Zn, Cu, As, Pb, Cd and total Hg) in the Mediterranean mussel, Mytilus galloprovincialis (L.). Based on their levels, the quality of Montenegro seawater for future mussel farming was estimated. The mussel M. galloprovincialis (L.) was collected from four sites in the Montenegrin costal area in the period of two years to determine trace element concentrations and to classify the quality of the coastal water and possible hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…By comparing the data from different Mediterranean regions (Table 2) it is possible to note that Hg concentrations observed in this study in the Adriatic Sea were higher than those observed by Markovic et al [13], along the southeastern Adriatic Coast Montenegro, and Gavrilovic et al [17] in Mali Ston (Croatia).…”
Section: Resultssupporting
confidence: 40%
See 1 more Smart Citation
“…By comparing the data from different Mediterranean regions (Table 2) it is possible to note that Hg concentrations observed in this study in the Adriatic Sea were higher than those observed by Markovic et al [13], along the southeastern Adriatic Coast Montenegro, and Gavrilovic et al [17] in Mali Ston (Croatia).…”
Section: Resultssupporting
confidence: 40%
“…As shown in Table 2, Cd levels were much lower than those reported for the Adriatic Sea [13,14] and Malesia market [15] but higher than Cd levels reported by Olmedo et al [16], for the Spain market.…”
Section: Resultsmentioning
confidence: 61%
“…Comparison of THg concentrations in mussels (Mytilus galloprovincialis) from different world seas. Data from: BENEDICTO et al, 2011;BILANDŽIĆ et al, 2016;BRIANT et al, 2017;CASTELLANI et al, 2015;CHEN et al, 2009;CLAISSE et al, 2001;CUBADDA et al, 2006;CULLAJ et al, 2006;FABBRI et al, 2006;FATTORINI et al, 2008;GALGANI et al, 2014;GORBI et al, 2008;KLJAKOVIĆ-GAŠPIĆ et al, 2006;KWON et al, 2014;LOCATELLI, 2003;LOCATELLI & MELUCCI, 2010;MARKOVIĆ et al, 2012;MOSCHINO et al, 2016;MZOUGHI & CHO-UBA, 2012;SPADA et al, 2013;STANKOVIĆ et al, 2011;TSANGARIS et al, 2013. Fig.…”
Section: Mercury In Mussels From Different Seasmentioning
confidence: 99%
“…Box-and-whiskers plots of the geographical distribution of THg in mussels (Mytilus galloprovincialis) from the Adriatic Sea. Data from BILANDŽIĆ et al, 2016;BLOOM et al, 2004;BOGDANOVIĆ et al, 2014;CASTELLANI et al, 2015;CATTANI et al, 1999;CORSI et al, 2011;CUBADDA et al, 2006;CULLAJ et al, 2006;DA ROS et al, 2000;DOMINIK et al, 2014;FABBRI et al, 2006;FATTORINI et al, 2008;FAVRETTO et al, 1997;GIORDANO et al, 1991;GORBI et al, 2008;JOVIĆ & STANKOVIĆ, 2014;KLJAKOVIĆ-GAŠPIĆ et al, 2006;KOSTA et al, 1978;LOCATELLI, 2003;LOCATELLI & MELUCCI, 2010;LOWE et al, 1995;MAJORI et al, 1991;MARKOVIĆ et al, 2012;MARTINČIĆ et al, 1987;MIEDICO et al, 2013;MIKAC et al, , 1989MIKAC et al, , 1996MOSCHINO et al, 2016;NAJDEK & SAPUNAR, 1987;NASCI et al, 1998;ODŽAK et al, 2000;RAMŠAK et al, 2012;SPADA et al, 2013;STANKOVIĆ et al, 2011;STORELLI & MARCOTRI-GIANO, 2001;TURK et al, 2007;WIDDOWS et al, 1997;ZATTA et al, 1992;ZVONARIĆ, 1991....…”
Section: Mercury In Adriatic Musselsmentioning
confidence: 99%
“…Typically, environmental studies are based on samples of air, water and soil. In many cases, particularly for the collection of heavy metals, there is a tendency to use animals as biomarkers of the environment [7,12,25,33,38]. Various groups of animals, including birds, are used in the monitoring of wetlands due to their specific role as a link in the elements of an ecosystem [36].…”
Section: Introductionmentioning
confidence: 99%